Voltage-Gated Calcium Channels and α-Synuclein: Implications in Parkinson’s Disease - Leandrou, Emmanouela; Emmanouilidou, Evangelia; Vekrellis, Kostas (Frontiers in Molecular Neuroscience, 2019)
α-synuclein (α-syn) is biochemically and genetically linked to Parkinson’s disease (PD) and other synucleinopathies. It is now widely accepted that a-syn can be released in the extracellular space, even though the mechanism of its release is still unclear. In addition, pathology-related aggregated species of α-synuclein have been shown to propagate between neurons in synaptically connected areas of the brain thereby assisting the spreading of pathology in healthy neighbouring neuronal cells. In neurons, calcium channels are key signaling elements that modulate the release of bioactive molecules (hormones, proteins, neurotransmitters) through calcium sensing. Such calcium sensing activity is determined by the distinct biophysical and pharmacological properties and the ability of calcium channels to interact with other modulatory proteins. Although the function of extracellular α-synuclein is currently unknown, previous work suggested the presence of a calcium-dependent mechanism for α-syn secretion both in vitro, in neuronal cells in culture, and also in vivo, in the context of a trans-neuronal network in brain. Mechanisms regulating extracellular a-syn levels may be of particular importance as they could represent novel therapeutic targets. We discuss here how calcium channel activity may contribute to a-syn aggregation and secretion as a pathway to disease progression in synucleinopathies.